Symbiotic Root-Endophytic Soil Microbes Improve Crop Productivity and Provide Environmental Benefits - Gary E. Harman; Norman Uphoff (Scientifica)
Plants should not be regarded as entities unto themselves, but as the visible part of plant-microbe complexes which are best understood as “holobiomes.” Some microorganisms when given the opportunity to inhabit plant roots become root symbionts. Such root colonization by symbiotic microbes can raise crop yields by promoting the growth of both shoots and roots, by enhancing uptake, fixation, and/or more efficient use of nutrients, by improving plants’ resistance to pests, diseases, and abiotic stresses that include drought, salt, and other environmental conditions, and by enhancing plants’ capacity for photosynthesis. We refer plant-microbe associations with these capabilities that have been purposefully established as enhanced plant holobiomes (EPHs). Here, we consider four groups of phylogenetically distinct and distant symbiotic endophytes: (1) Rhizobiaceae bacteria; (2) plant-obligate arbuscular mycorrhizal fungi (AMF); (3) selected endophytic strains of fungi in the genus Trichoderma; and (4) fungi in the Sebicales order, specifically Piriformospora indica. Although these exhibit quite different “lifestyles” when inhabiting plants, all induce beneficial systemic changes in plants’ gene expression that are surprisingly similar. For example, all induce gene expression that produces proteins which detoxify reactive oxygen species (ROS). ROS are increased by environmental stresses on plants or by overexcitation of photosynthetic pigments. Gene overexpression results in a cellular environment where ROS levels are controlled and made more compatible with plants’ metabolic processes. EPHs also frequently exhibit increased rates of photosynthesis that contribute to greater plant growth and other capabilities. Soil organic matter (SOM) is augmented when plant root growth is increased and roots remain in the soil. The combination of enhanced photosynthesis, increasing sequestration of CO2 from the air, and elevation of SOM removes C from the atmosphere and stores it in the soil. Reductions in global greenhouse gas levels can be accelerated by incentives for carbon farming and carbon cap-and-trade programs that reward such climate-friendly agriculture. The development and spread of EPHs as part of such initiatives has potential both to enhance farm productivity and incomes and to decelerate global warming.